2022
DOI: 10.1021/jacs.1c10584
|View full text |Cite
|
Sign up to set email alerts
|

Effective Storage of Electrons in Water by the Formation of Highly Reduced Polyoxometalate Clusters

Abstract: Aqueous solutions of polyoxometalates (POMs) have been shown to have potential as high-capacity energy storage materials due to their potential for multi-electron redox processes, yet the mechanism of reduction and practical limits are currently unknown. Herein, we explore the mechanism of multi-electron redox processes that allow the highly reduced POM clusters of the form {MO 3 } y to absorb y electrons in aqueous solution, focusing mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 33 publications
1
46
0
1
Order By: Relevance
“…These features broaden the application of POMs and make them good candidates for energy storage and conversion. [136][137][138][139][140][141] Recently, a new kind of RAILs has been prepared by replacing the anions of ILs with polyoxometalates, which are described as POM-ILs. [142][143][144] This kind of RAILs combines the properties of both POMs and ILs, which gives them the characteristics of tunable properties and ease of processing.…”
Section: Railsmentioning
confidence: 99%
“…These features broaden the application of POMs and make them good candidates for energy storage and conversion. [136][137][138][139][140][141] Recently, a new kind of RAILs has been prepared by replacing the anions of ILs with polyoxometalates, which are described as POM-ILs. [142][143][144] This kind of RAILs combines the properties of both POMs and ILs, which gives them the characteristics of tunable properties and ease of processing.…”
Section: Railsmentioning
confidence: 99%
“…To further explore the difference between oxidized and reduced Dawson POM cluster, Chen et al investigated oxidized and highly reduced POMs by small-angle X-ray scattering (SAXS). [87] By comparing the SAXS of oxidized state of POM {P 2 W 18 } and reduced state of POM {P 2 W 18 }-18e with different cations (K + , Na + and Li + ), it was found that the coulomb peak of K-{P 2 W 18 }-18e and Na-{P 2 W 18 }-18e were almost shielded while the coulomb peak of Li-{P 2 W 18 }-18e was partially shielded (Figure 4b) between q = 0.1 ~0.3 Å À 1 . The appearance of the coulomb peak is related to the orderly arrangement of the POM species in the solution, and when it disappears, it represents the aggregation behaviour of the POM.…”
Section: Spectroscopy Characterization Of Polyoxometalate Redox Behav...mentioning
confidence: 99%
“…3,15,16 In context, a comprehensive study of the physical−chemical events occurring along their electrochemical reduction appears as crucial from a fundamental aspect but also for (i) their rational integration as active components in batteries (Li-ion, Na-ion, or redox flow) and (ii) their use as redox mediators in electro(photo)catalytic processes. 3,5,15 The Keggin-type silicotungstate α-[Si(W VI 3 O 10 ) 4 ] 4− (abbreviated as SiW 12 -0), containing a central SiO 4 tetrahedron surrounded by four triads {W 3 O 13 } mutually connected through corner-shared junctions, represents a popular charge carrier used in ground-breaking electrochemical devices. 16−19 Nevertheless, pioneered works have revealed that its electrolysis at controlled potential in an acidic solution can lead to well-defined six-electron-reduced POMs [Si-(W IV 3 O 7 (H 2 O) 3 )(W VI 3 O 10 ) 3 ] 4− (notated SiW 12 -VI′) in which 5d electrons are localized in three metal−metal bonds, forming a W IV -based trinuclear cluster.…”
Section: ■ Introductionmentioning
confidence: 99%